Teacher Education and School Resource Management: Any Relevance in Sustainable National Development in Developing Countries Like Nigeria? - Oluwatoyin, Fashiku, Christopher; Abubakar, Yusuf Abiola (American Journal of Education and Learning, 2019)
The place of teachers in school resource management is so significant that it cannot be swept under the carpet. It is as pertinent in national development in not only Nigeria as a developing country but the entire countries of the world. More so that no quality of a nation’s education can rise above the quality of her teachers. The paper discussed: concept of teacher education, school resource management and school resources, national development as well as difficulties faced by teachers in Nigeria in schools’ resource management. It was concluded in the paper that government in developing countries, Nigeria in particular pay very little attention to this and that if the problems are not promptly attended to, might bring a total crash in the standard of education in the country, and this will impede the desired development in Nigeria. It was therefore recommended in the paper amongst others that government should provide adequate resources for use in the institutions of learning and should institute an all-embracing staff mentainance programme in Nigeria.